Fatigue load suppression during active power control process in wind farm using dynamic-local-reference DMPC. (January 2022) - Yao, Qi; Hu, Yang; Zhao, Tianyang; Guan, Yuanpeng; Luo, Zhiling; Liu, Jizhen
Abstract: Since the established wind farms (WFs) have a strong demand for reducing maintenance costs, the fatigue load suppression of wind turbines (WTs) has become more important in WFs. To suppress the fatigue load during operation, the traditional schemes are tried by allocating the optimized power setting value to each WT, which does not directly point to the key operating parameters that affect fatigue. In response to this, an advanced WT control model with two-degree-of-freedom (2Dof) is applied in this paper to ensure that the generator torque and pitch angle (two key parameters affecting fatigue load) of each WT are directly controlled. In order to achieve effective control of the above two parameters in multiple WTs, a hierarchical distributed control architecture with dynamic-local-reference is proposed to jointly optimize the above two configurable parameters at both the WT and WF levels. Several cases are compared to verify the proposed method, and simulation results show that the proposed 2Dof control model for WT and distributed control framework for WF can significantly reduce the fatigue load of each WT while completing the active power command of the whole WF. Highlights: Two-degree-of-freedom wind turbine control model is applied in wind farms. Distributed model predictive control (DMPC) framework is adopted. Dynamic WT reference power algorithm is proposed based on DMPC. Fatigue load of all wind turbines in the wind farm are significantly reduced.